Development Of Automated Coolant Supply (ACS) System In Improving Cutting Performance For CNC Milling Machining - Wan Md Hatta, Wan Nur 'Izzati (2019)
CNC machine is an industrial manufacturing machine that is used to improve quality and productivity of product. There are two ways of applying coolant in general, which are dry machining and wet cooling machining. Therefore, some researches had been done in order to get information about the method involved. It had been found that there are some disadvantages for both techniques and this had bring differents result to the workpiece, tooling, health and also environment. Moreover, the used of wet cooling technique causes waste since the workpiece only need a small amount of coolant. Then, increase in temperaturedue to the friction and energy lost can lead the cutter to be unsharpened and it will affect high power usage and poor in surface finishing. Hence, the idea of using PLC that inspired as the control system plays the main role in developing the modern technology and industry. The purpose of this project is to design an Automated Coolant Supply (ACS) System based on Programmable Logic Control for CNC milling machine, to identify the best interval time for the performance of the proposed Automated Coolant Supply (ACS) System and to analyse angle positioning and nozzle distance of 3 difference types of nozzle in the CNC machining under Automated Coolant Supply (ACS) System.The structure of this project involved development in software and hardware. Then, the adjusted timer to control the coolant supply is by applying the washing machine inlet to control valve. Three experiments involved in this study which are Experiment 1 started by finding the best combination of parameters using Taguchi method. Then, Experiment 2 is testing the performance of the machine by using 1s to 60s interval time. After the best interval time for the surface roughness had been investigated, 3 differences shape of nozzle with 8 difference positions of nozzle and 7 distances of nozzle are used to run Experiment 3.Performance involve the study in shape and position of nozzle are analysed in order to measure the relationship of nozzle criteria force. It had been found that this ACS method is succesful since interval time 25s has the best surface roughness value with the lowest quantity of coolant used. The data and graph could be seen in Experiment 2 results. Meanwhile, it is supported by using 3 differences shape of nozzle. All of the shapes, angles and distances of nozzle involved give various results. Hence, it can be concluded that this ACS system is successful and it is recommended to be used in future.